A national cross-sectional study on breakfast skipping-related factors and comparison of nutritional status according to breakfast skipping in older adults based on the 8th Korea National Health and Nutrition Examination Survey (KNHANES, 2020) - Anna Han; Yean Jung Choi (Elsevier, 2024)
Objectives: This study aimed to compare the distinct socio-ecological characteristics, nutritional status, and nutrient intake quality of the older adults based on breakfast skipping (EBF, eating breakfast vs. SBF, skipping breakfast). This study also investigated the association between breakfast skipping, socioecological features, and quality of nutrient consumption. Method: From the 8th Korea National Health and Nutrition Examination Survey (KNHANES, 2020), data of 92,093 subjects aged ≥ 65 years old (male: 43,910 and female: 48,183) having data with eating habits, such as nutrient intake and skipping breakfast were analyzed. Results: The average age of SBF was markedly lower than EBF. EBF had a lower employed status, education level, heavy alcohol intake frequency, smoking, and eating out regularly than SBF. Compared to EBF, SBF showed a significantly higher BMI and waist circumference. Moreover, EBF showed a markedly higher average intake in energy, protein, fiber, calcium, and iron compared with SBF, while SBF had a noticeably higher mean intake in fat, saturated fat, and sugar. In addition, SBF had a significantly reduced mean adequacy ratio (MAR, adjusted OR: 0.260 [95% CI: 0.245−0.276]) and the value of index nutritional quality (INQ, adjusted OR: 0.847 [95% CI: 0.799−0.898]) compared with EBF. Discussion: There were distinct socioecological features and nutritional conditions of older adults relying on breakfast skipping; and a strong association between breakfast skipping, socioecological parameters, and nutrient intake quality. These observations provide the significance of breakfast skipping in the nutritional status of older adults and offer fundamental information for nutritional education and implications for older adults.